PENGARUH KONFLIK PEKERJAAN-KELUARGA TERHADAP KEPUASAN KERJA DAN KEPUASAN HIDUP (STUDI PADAPEREMPUAN ETNIS BALI YANG BEKERJA DI KOTA MATARAM) - Siti Nurmayanti; Dwi Putra Buana Sakti; I Nyoman Nugraha Ardana Putra; Laila Wardani (Distribusi - Journal of Management and Business, 2018)
The Balinese, wherever they live either individually or in groups, will always carry out their lives as in the ancestral area of ​​Bali Island. Implementation of the livelihood arrangements that have been regulated and inherited by Balinese ethnic ancestors apply to both men and women. Of course this adds a role for Balinese women, especially to those who work. Balinese ethnic women who work are faced with fulfillment of obligations in various roles. This condition if it can not be aligned, can lead to conflict Conflict that arise can be a work-family conflict that can impact on job satisfaction and life satisfaction.     This study aims to analyze the influence of conflict of family work on job satisfaction of ethnic Balinese women who work and analyze the influence of conflict of family work to life satisfaction of Balinese ethnic women who work .. The paradigm used in this research is a positivist paradigm with quantitative method as the right design for achieve research objectives. Through this approach the researcher distributed a structured questionnaire aimed at obtaining data to be analyzed. to 149 Balinese women respondents in Mataram working, All data were analyzed using Partial Least Squre (PLS). The result of the research shows that the conflict of family work negatively and significantly influence the work satisfaction of the working ethnic Balinese women and the conflict of family work have a negative and significant effect to the satisfaction of life of Balinese ethnic women who work.